The Corporate Reputation of Multinational Corporations An Analysis of Consumers' Perceptions of Corporate Reputation and its Effects Across Nations - Huber, Cathrin (Handel und Internationales Marketing Retailing and International Marketing,, 2018)
Cathrin Huber investigates the reputation of multinational corporations and provides novel insights and important implications for researchers and managers based on theoretical considerations and empirical analyses. She shows that country-specific factors like cultural or political factors, but also institutional differences between countries as well as firm-specific resources in a country influence the corporate reputation-consumer behavior relationship. Additionally, an overview of the main cultural approaches and how they influence consumers' corporate reputation perceptions is given. Contents The Moderating Role of Institutional Country Differences on Corporate Reputation Effects Institutional Country Distances and Firm-specific Resources as Moderators of Corporate Reputation Effects National Culture Approaches as Antecedents of Corporate Reputation Perceptions Target Groups Students and researchers focusing on international marketing, corporate branding and in particular on corporate reputation Executives and managers interested in the successful management of corporate brands About the Author Dr. Cathrin Huber received her doctoral degree from the University of Trier, where she worked at the chair for Marketing and Retailing.